(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to clarify the role of educational games in developing certain moral values among kindergarten children from the perspective of teachers. The researcher employed the descriptive method and applied a questionnaire to (14) teachers in several kindergartens. The results revealed that educational games contribute significantly to enhancing children’s moral values, such as respect, avoiding inappropriate language, cooperation, honesty, love of school, self-discipline, and positive participation. The findings also indicated that children interact more effectively with values when they are presented through play rather than through traditional teaching methods. The study confirmed that educational games are an effective tool for instilling moral values in kindergarten children. It recommends integrating them systematically into educational plans and training teachers to design and implement such games within daily activities.